Legal Accountability and Innovative Strategies in Enhancing Healthcare Workers’ Compliance with the Implementation of Informed Consent and Refusal in Midwifery Services in Medan City - Tambunan, Edo Maranata; Harahap, Sridama Yanti; Khalishah, Khansa; Lubis, Atika Rahmadhani; Sitompul, Briyan Valentino (Dinasti Research, 2025)
The implementation of informed consent and refusal is a legal, ethical, and professional obligation in midwifery services, aimed at protecting patients’ rights and mitigating the risks of disputes and legal liabilities for healthcare providers. However, its implementation still faces serious challenges. The objective of this study is to assess the level of compliance among healthcare workers in implementing informed consent and refusal, and examine aspects of legal accountability and innovative strategies supporting midwifery services in Medan City. The research method used in this study employed normative juridical and empirical methods with a descriptive-analytical approach. Data were collected through purposive sampling using the Slovin formula and analyzed both quantitatively and qualitatively. Based on the survey results, the majority of respondents were categorized as compliant (66.7%), although one-third were non-compliant (33.3%). Institutional support through Standard Operating Procedures (SOPs) was relatively strong; however, legal training and the adoption of digital documentation remained limited, resulting in weak legal awareness and substantive compliance. These findings underscore the importance of strengthening legal capacity through the dissemination and enhancement of health law literacy. Furthermore, standardization of implementation and the acceleration of digital transformation are required to minimize legal risks and improve the quality of services.